Criminalizing the recruitment of children in light of the Statute of the International Criminal Court - Boubertakh, Naima (Journal of Human Sciences, 2022)
The category of children is the most vulnerable to the violation of their rights, especially in times of armed conflict, It didn’t stop on depriving them of their basic and well-known rights, but they have been exploited the cruelest exploitation without taking into consideration their childhood and their physical and psychological weakness, by recruiting them into international and non-international armed conflicts, by their direct and indirect use in military operations, therefore, the 1998 Rome Agreement criminalized and classified the recruitment of children as crimes of war that require responsibility and punishment, and fall within the subject matter jurisdiction of the International Criminal Court, in accordance with Articles (5) and (8) of its Statute.